The Influence of Implementing Student Facilitator and Explaining (SFAE) Learning Model on Student Learning Outcomes Assisted by Dakonmatika Learning Media - Rahmatullah Bin Arsyad; Sitti Muayada Haris; Zakiyah Anwar; Muhammad Fathurrahman; Muhammad Syahrul Kahar; Erpin Said (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Students' motivation to study mathematics was essential for improving their learning outcomes in the subject. Integrating the cooperative learning model of Student Facilitator and Explaining (SFAE) with the Dakonmatika learning media represents an innovative blend of group learning and the traditional Indonesian game of Dakon or Congklak. This research aims to determine the effect of using the SFAE learning model assisted by Dakonmatika media on students' mathematics learning outcomes. The study employs a quantitative method with a Quasi-Experimental design in the form of The Nonequivalent Pretest-Posttest Control Group Design. The subjects of this study were 54 students from Muhammadiyah 2 Elementary School in Sorong City, divided into two classes: an experimental class of 29 students and a control class of 25 students. The research findings indicated that, based on the previously described data analysis and discussion of the multiple linear regression test, a significance value of 0.019 < 0.05 was obtained. According to the decision-making criteria, H0 was rejected. Moreover, from the t-test table, the calculated value (2.477) was greater than the table value (2.05553), meaning that t_calculated > t_table. It implied that the application of the SFAE learning model with the assistance of Dakonmatika media has a significant impact on the mathematics learning outcomes of fifth-grade students at Muhammadiyah 2 Elementary School in Sorong City. The implication of this study was that the integration of the Student Facilitator And Explaining (SFAE) learning model with daconmatics media has great potential in improving the quality of mathematics learning in schools.